2017
DOI: 10.1155/2017/1897825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride Varnish Containing CPP-ACP on Preventing Enamel Erosion

Abstract: This study aimed to investigate the effect of a fluoride varnish with added casein phosphopeptide-amorphous calcium phosphate treatment on the prevention of enamel erosion, and it compared the results with those of other fluoride varnishes. Fifty enamel specimens obtained from bovine incisors were randomly divided into five groups (n = 10) based on the type of surface pretreatment used: intact enamel (Group 1); intact enamel+erosive cycles (Group 2); intact enamel+MI varnish+erosive cycles (Group 3); intact en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 34 publications
3
33
2
1
Order By: Relevance
“…The same was found in group 2 where fluoride varnish does not provide a physical or mechanical barrier against pH cycle. The result is compatible with Bayrak et al, [51] despite the difference in acidic challenge. Tricalcium phosphate which added to flouride varnish is a hybrid material formed by a milling technique that fuses beta tricalcium phosphate and sodium lauryl sulfate or fumaric acid [4] .…”
Section: Discussionsupporting
confidence: 92%
“…The same was found in group 2 where fluoride varnish does not provide a physical or mechanical barrier against pH cycle. The result is compatible with Bayrak et al, [51] despite the difference in acidic challenge. Tricalcium phosphate which added to flouride varnish is a hybrid material formed by a milling technique that fuses beta tricalcium phosphate and sodium lauryl sulfate or fumaric acid [4] .…”
Section: Discussionsupporting
confidence: 92%
“…This is because CPP‐ACFP exhibits superior remineralization properties to conventional fluoride varnishes (Ekambaram et al, ; Naveena, Nagarathana, & Sakunthala, ). Several studies compared MI Varnish and Duraphat Varnish to different caries assessment methods, and MI varnish was observed to be more effective (Bayrak, Tuloglu, Bicer, & Sen Tunc, ; Cochrane, Saranathan, Cai, Cross, & Reynolds, ; Majithia et al, ; Pithon et al, ). In contrast to the study by Shahmoradi, Hunter, and Swain (), which compared the remineralization efficacy of Duraphat and MI varnishes with μCT, the present study showed that MI varnish had a higher remineralization than Duraphat varnish.…”
Section: Discussionmentioning
confidence: 99%
“…MI Varnish, which has 22 000 ppm F, could provide better protection than MI Paste Plus (GC America, Alsip, Ill, USA), which has only 900 ppm F . Fluoride varnish containing CCP‐ACP has been shown to be superior to other varnishes in increasing the acid resistance of enamel, and was therefore chosen for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The anticariogenic activity of CPP‐ACP, as well as its synergistic effect with fluoride, have been demonstrated. MI Varnish enhances enamel's resistance against acidity and rehardens early carious lesions . Furthermore, it releases phosphate and greater amounts of fluoride and calcium ions than other varnishes …”
Section: Introductionmentioning
confidence: 99%